Cystine dimethyl ester cross-linked PEG-poly(urethane-urea)/nano-hydroxyapatite composited biomimetic scaffold for bone defect repair. Issue 3 (11th February 2020) - Zhou, Zhangzhe; Wang, Yimeng; Qian, Yuqing; Pan, Xiangqiang; Zhu, Jian; Zhang, Zhengbiao; Qian, Zhonglai; Sun, Zhiyong; Pi, Bin
Abstract: Polyurethane (PU) and polyurea (PUA) materials have shown significant potential for application in tissue repair. Herein, we design a glycerol ethoxylate (PEG)-based poly(urethane-urea) for bone tissue repair. The polymer precursor was prepared from the reaction of PEG and isophorone diisocyanate (IPDI). The cystine dimethyl ester was used as a cross-linker for the preparation of poly(urethane-urea) elastomers. The material was further strengthened by physical blending of nano-hydroxyapatite (nHA). The physical and biological properties of final material were evaluated by mechanical testing, scanning electron microscopy characterization, degradation tests, cell proliferation and cell differentiation assays. The obtained scaffolds showed good mechanical strength, excellent biocompatibility and osteogenic capability. All the evidences demonstrated that this type of materials has good prospects for bone tissue repair application.